'BROTHERS IN ARMS'?: The American and British Coalition on the Western Front, 1918 - Yockelson, M (Department of Management and Security Analysis, 2009)
This dissertation examines in detail, the organisation, training and operations of the 27 th and 30th American Divisions during the period of Summer 1917 to the announcement of an armistice in November 1918. Particular emphasis is placed on the two divisions after they were attached to the 11 American Corps. especiallý their experience with the British Expeditionary Force in 1918, and the training received under the supervision of British officers. The 11 American Corps was unique in that it spent its entire service in France in the British sector. Originally it was composed of 10 divisions, but eight of these were removed by the commander of the American Expeditionary Forces, Gen. John. J. Pershing. The divisions were transferred to the First American Army and operated entirely independent of 11 American Corps. The týýo American divisions that h, oth remained with the British, the 27t and -3 , relied heavily upon their coalition partners for advice in training, supplies, equipment, food and more importantly, tactical leadership. Although General Pershing forbade American divisions from being th -, oth amalgamated into Allied armies, in reality, the 27 and -) Divisions became part of the BEF, especially the Fourth Arrný during the final campaigns of the war. Despite its attachment to arguably the best fighting force on the Western Front in 1918, the 11 American Corps suffered heavý casualties during its limited operational experience and. in many ways. failed to take advantage of lessons learned by the British Army during its campaigns of 1916-1917. This dissertation concludes that the relationship between the two American divisions and their British ally was in the end result a success. By allowing the 27 th and 30'hDivisions to remain behind with the BEF, Pershing provided the British with more than 50,000 able American troops to use at the front. Thus the tNNo ,a llies became Brothers-in-Arms.
Keywords: World War I; Western Front; World War, 1939-1945 - Campaigns - Western Front; Soldiers - US and UK - Biography